Isolation, screening and molecular characterization of phytase producing microorganisms to discover the novel phytase - Nezhad, Nima Ghahremani (Springer Nature, 2023)
Due to a lack of endogenous phytase enzymes in monogastric animals, exogenous phytases are employed in the animal feed industry. Phytases catalyze the hydrolysis of phytic acid and its salts (phytate) from plant-based animal feed, to supply phosphorus to monogastric animals and decrease the anti-nutritional effects of phytic acid. This study aimed to discover the new phytase with optimum activity at acidic pH range and 40 °C for the poultry feed industry. In the current investigation, phytase-producing microorganisms were isolated from different sources and locations, demonstrating that ten of the isolates are attributed to bacterial strains, and one of which is a yeast strain. Phytase-producing microorganisms were screened based on qualitative and quantitative assays. Additionally, molecular characterization was carried out based on sequencing of amplified 16S rRNA and nuclear ribosomal transcribed spacer (ITS) genes. Then, degenerate primers were designed to amplify the histidine acid phosphatase gene from potential isolates to find the new natural variant of phytase. Quantitative assays were carried out to find pH and temperature profiles at pH ranges between 2 and 7, with a 0.5 interval, and a range of temperatures from 30 °C to 90 °C, with a 10 °C interval. The results from crude enzymes demonstrated the extracellular phytase activities of isolates with different optimum pH and temperatures ranging from 4 to 6.5 and 40 °C–60 °C, respectively. Moreover, the range of optimum phytase activities of isolates was between 194.21 mU/mL and 381 mU/mL. Sequencing analysis of 16S rDNA and nuclear ribosomal transcribed spacer (ITS) genes revealed that six out of the eleven isolates are attributed to the Acinetobacter genus, two of which are affiliated with Enterobacter genus. One is affiliated with the Pseudomonas genus; one of them is affiliated with Escherichia, and another is affiliated with Saccharomyces. Finally, a new native histidine acid phosphatase gene (PhySc) was detected and amplified from the SPA isolate by designing degenerate primers. This showed a 99.50 identity with PHO5 from Saccharomyces cerevisiae YJM993 with an accession number of CP004601.2.